Prevalence and risk factors for type 2 diabetes mellitus in women with gestational diabetes mellitus: a systematic review and meta-analysis - Chen, Kaiqi; Tang, Lichao; Wang, Xinwei; Li, Yunhua; Zhang, Xijian; Cui, Shikui; Chen, Wei; Jin, Zhao; Zhu, Danping (Frontiers in Endocrinology, 2024)
IntroductionThis study aims to explore the risk factors in the progression of gestational diabetes mellitus (GDM) to type 2 diabetes mellitus (T2DM).Material and methodsRelevant studies were comprehensively searched from PubMed, Web of Science, Cochrane Library, and Embase up to March 12. Data extraction was performed. Differences in risk factors were presented as odds ratios (OR) and corresponding 95% confidence intervals (CI). The quality of the included studies was assessed through the Newcastle-Ottawa Scale and the Agency for Healthcare Research and Quality scale.ResultsThis meta-analysis encompassed 46 studies involving a total of 196,494 patients. The factors most strongly associated with the risk of developing T2DM following GDM were the use of progestin-only contraceptives (odds ratio [OR]: 2.12, 95% confidence interval [CI] = 1.00–4.45, P = 0.049), recurrence of GDM (OR: 2.63, 95% CI = 1.88–3.69, P < 0.001), insulin use during pregnancy (OR: 4.35, 95% CI = 3.17–5.96, P < 0.001), pre-pregnancy body mass index (BMI) (OR: 2.97, 95% CI = 2.16–4.07, P < 0.001), BMI after delivery (OR: 4.17, 95% CI = 2.58–6.74, P < 0.001), macrosomia (OR: 3.30, 95% CI = 1.45–7.49, P = 0.04), hypertension (OR: 5.19, 95% CI = 1.31–20.51, P = 0.019), and HbA1c levels (OR: 3.32, 95% CI = 1.81–6.11, P < 0.001). Additionally, age (OR: 1.71, 95% CI = 1.23–2.38, P = 0.001), family history of diabetes (OR: 1.47, 95% CI = 1.27–1.70, P < 0.001), BMI during pregnancy (OR: 1.06, 95% CI = 1.00–1.12, P = 0.056), fasting blood glucose (FBG) (OR: 1.58, 95% CI = 1.36–1.84, P < 0.001), 1-hour oral glucose tolerance test (OGTT) (OR: 1.38, 95% CI = 1.02–1.87, P = 0.037), and 2-hour OGTT (OR: 1.54, 95% CI = 1.28–1.58, P < 0.001) were identified as moderate-risk factors for the development of T2DM.ConclusionThe systematic review and meta-analysis identified several moderate- to high-risk factors associated with the progression of T2DM in individuals with a history of GDM. These risk factors include the use of progestin-only contraceptives, pre-pregnancy BMI, BMI after delivery, macrosomia, hypertension, persistently elevated levels of HbA1c, fasting blood glucose (FBG), 1-hour and 2-hour oral glucose tolerance tests (OGTT), age, and family history of diabetes. Our findings serve as evidence for the early prevention and clinical intervention of the progression from GDM to T2DM and offer valuable insights to guide healthcare professionals in formulating customized management and treatment strategies for female patients with diverse forms of GDM.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024545200.